2012
DOI: 10.1161/hypertensionaha.112.201087
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Role of Epoxyeicosatrienoic Acids in the Regulation of Basal Conduit Artery Diameter During Essential Hypertension

Abstract: In young healthy subjects, epoxyeicosatrienoic acids synthesized by endothelial cytochrome P450 epoxygenases maintain basal conduit artery diameter during altered NO availability. Whether this compensatory mechanism is effective during essential hypertension is unknown. Radial artery diameter, blood flow, and mean wall shear stress were determined in 14 nontreated essential hypertensive patients and 14 normotensive control subjects during 8 minutes of brachial infusion for inhibitors of cytochrome P450 epoxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Endothelial dysfunction plays a crucial role in the pathogenesis of various cardiovascular complications, including hypertension (Wallace et al, ) and atherosclerosis (Bellien, Remy‐Jouet, et al, ). Endothelial dysfunction manifests as damage to the vascular tone and homeostasis and is responsible for significant morbidity and mortality in patients of cardiovascular diseases (CVDs; Bellien, Iacob, et al, ; Modena, Bonetti, Coppi, Bursi, & Rossi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction plays a crucial role in the pathogenesis of various cardiovascular complications, including hypertension (Wallace et al, ) and atherosclerosis (Bellien, Remy‐Jouet, et al, ). Endothelial dysfunction manifests as damage to the vascular tone and homeostasis and is responsible for significant morbidity and mortality in patients of cardiovascular diseases (CVDs; Bellien, Iacob, et al, ; Modena, Bonetti, Coppi, Bursi, & Rossi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In normal and hypertensive subjects treated with aspirin and N G -monomethyl-L-arginine to block vascular prostaglandin and nitric oxide synthesis, bradykinin increases forearm blood flow that is inhibited by the CYP inhibitor sulfaphenazole (45). Other studies document the dilator role of EETs in humans and human arteries (38, 43, 46). …”
Section: Summary Of Cardiovascular Actions Of the Eetsmentioning
confidence: 84%
“…Another group reported no difference in basal plasma concentrations of EETs between healthy control subjects and hypertensive patients, but an impairment in induced EET release, in combination with NO and reactive oxygen species balance, and the endothelin-1 pathway contributed to endothelial dysfunction of conduit arteries (measured by flow mediated dilatation) in essential hypertensives [125]. The same group later demonstrated that inhibition of CYP450 reduced basal conduit arterial diameter only in healthy subjects, and not in essential hypertensives, but it did not change resistance arterial flow in both groups [55]. This is consistent with another study, which reported that a CYP450 inhibitor did not change basal flow within both normotensive and hypertensive patients, but conversely, it significantly blunted both acetylcholine and bradykinin induced flow only in hypertensives.…”
Section: Eet Signalling In Cardiovascular Diseasementioning
confidence: 93%
“…The physiological role of EETs in maintaining basal tone appears to be limited. Basal flow response was investigated in six human in vivo studies, and five reported no change in basal flow in healthy subjects , and one reported 13% and 17% reduction in response to fluconazole in 26 healthy subjects and seven patients with cardiovascular risk factors, respectively . Three of these in vivo studies assessed basal tone in fewer than 10 subjects , and thus were significantly underpowered.…”
Section: The Role Of Eets In Regulating Vascular Tonementioning
confidence: 99%
See 1 more Smart Citation